Influence of bias power and doping of Si on hardness and toughness of CrAlN - Chan, Kristel Hui Yan. (2011)
This project focused on the study of the influence of bias power and concentration of doped silicon on the hardness and toughness of CrAlN thin films. Reactive magnetron sputtering was used to prepare CrAlN and CrAlSiN thin films by sputtering the CrAl target and co-sputtering CrAl/Si targets respectively in a gas mixture of argon and nitrogen. There were two parts in this study. For CrAlN thin films, the effect of bias power was studied by varying the degrees of bias power during sputtering. For CrAlSiN thin films, the effect of silicon concentration was studied by doping different amounts of silicon contents.